2000
DOI: 10.1038/77827
|View full text |Cite
|
Sign up to set email alerts
|

Epitope affinity for MHC class I determines helper requirement for CTL priming

Abstract: We show here that priming and memory generation of antigen-specific CD8+ cytotoxic T lymphocytes (CTL) does not require help if the immunogen binds major histocompatibility complex (MHC) class I molecules with high affinity. This conclusion was based on the study of three chemically distinct optimal length CTL epitopes with high affinity for the restriction element Kb. In contrast, when two subdominant epitopes with intermediate MHC binding affinity were studied, either a class II MHC-restricted T helper cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 45 publications
5
58
0
Order By: Relevance
“…Thus, the correlation shown here between T cell help, frequency of long-term memory CTLp and protection is compelling evidence of the longterm immunological advantage offered by T cell help during priming. Obviously, these considerations are only relevant to the long-term consequences of priming by epitope-based immunization [31], including those utilizing helper-independent analogue CTL peptides [32]. Whether or not in our model high CTLp frequencies require persistent antigen [33] was not studied, but one cannot exclude that transgenic Ig may be stored on follicular DC as a long-term antigen depot [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the correlation shown here between T cell help, frequency of long-term memory CTLp and protection is compelling evidence of the longterm immunological advantage offered by T cell help during priming. Obviously, these considerations are only relevant to the long-term consequences of priming by epitope-based immunization [31], including those utilizing helper-independent analogue CTL peptides [32]. Whether or not in our model high CTLp frequencies require persistent antigen [33] was not studied, but one cannot exclude that transgenic Ig may be stored on follicular DC as a long-term antigen depot [34].…”
Section: Discussionmentioning
confidence: 99%
“…This requirement may reflect the low affinity of the CD8 ϩ repertoire that is available for response to a self-Ag. It was recently demonstrated that one factor that is determinative of CD4 dependence of a CD8 response is that stability of the peptide-class I complex (38). It is likely that TCR affinity plays a similar role in determining the stability of the TCR-peptide-MHC complex.…”
Section: Discussionmentioning
confidence: 99%
“…They include antigen-specific features, such as nature and concentration of the immune-stimulating materials [46] or T-cell intrinsic characteristics, such as antigen precursor frequency [47].…”
Section: Discussionmentioning
confidence: 99%